Legal Protection Against Bank Customers in Review of Banking Laws - Dewi, Sri; Hulzannah, Miftah; Panggabean, Maria; Afri Rizki, Riki; Sriono, Sriono (CV. Inara, 2020)
Legal protection for customers is reviewed in terms of banking laws and regulations, such as Law Number 21 of 2008 concerning Islamic banking. Both Islamic banks and conventional banks with regulatory control must comply with general banking regulations. Act Number 7 of 1992 concerning Banking. The Banking Law which regulates amendments to Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1999. there is an obligation for banks to become members of the Deposit Insurance Corporation (LPS) so as to provide protection for depositors customers against their deposits and the existence of customer rights conduct customer complaints, and use banking mediation forums for simple, cheap, and fast dispute resolution. Legal protection for customers in terms of the Consumer Protection Act lies in the obligation for banks to heed the procedure for making standard clauses.Settings via The Consumer Protection Law which is closely related to legal protection for customers as banking consumers is the provision regarding standard clauses. Meanwhile, from the laws and regulations in the banking sector, the provisions that provide legal protection for bank customers as consumers include the introduction of the Deposit Insurance Corporation (LPS) in Law Number 10 of 1998. At the technical level the legal umbrella protecting customers includes the existence of arrangements regarding the settlement of customer complaints and banking mediation in a Bank Indonesia Regulation (PBI).